DNA Methylation of Tumor Suppressive miRNAs in Non-Hodgkin’s Lymphomas - Yim, Rita L.; Kwong, Yok L.; Wong, Kwan Yeung; Chim, Chor Sang (Frontiers in Genetics, 2012)
In addition to histone modification, DNA methylation is the other form of epigenetic alteration leading to heritable phenotypic changes of cells with functional consequences. DNA methylation is important in early embryonic development, stem cell differentiation, and tissue-specific gene expression in somatic cells. In normal cells, promoter-associated CpG islands are generally unmethylated except in X-chromosome inactivation or genomic imprinting. In cancer, tumor cells are characterized by global hypomethylation but locus-specific hypermethylation of promoter-associated CpG islands, resulting in gene silencing. MicroRNAs (miRNAs) are short, non-coding RNA sequences of 18-25 nucleotides, leading to translational repression of multiple protein-coding mRNAs by sequence-specific binding to the 3’ untranslated region. Depending on the genes that are targeted by the miRNA, miRNA can be tumor suppressive if an oncogene is being targeted, and conversely, oncogenic when a tumor suppressive gene is targeted. Recently, aberrant methylation of tumor suppressive miRNAs has been reported in different types of cancers including lymphomas. Herein, we summarize the recent literature of aberrant DNA methylation of tumor suppressive miRNAs in non-Hodgkin’s lymphomas (NHLs), including miRNA methylation in the pathogenesis of specific NHL subtypes, such as natural killer (NK)/T-cell, gastric mucosa-associated lymphoid tissue, anaplastic large cell or Burkitt’s lymphoma and the studies of miRNA methylation in B-, T- or NK-cell lymphomas by candidate miRNA approach